Expanding congenital abnormalities of the kidney and urinary tract (CAKUT) genetics: basonuclin 2 (BNC2) and lower urinary tract obstruction - Fernandez-Prado, Raul; Kanbay, Mehmet; Ortiz, Alberto; Perez-Gomez, Maria Vanessa (Annals of Translational Medicine, 2019)
CKD is characterized by chronic (>3 months), often irreversible, evidence of kidney injury or dysfunction with consequences for health (1). A diagnosis is made in the presence of decreased glomerular filtration rate (GFR) or if there is analytical (most commonly pathological albuminuria), histological or imaging evidence of kidney injury. The criterion “with consequences for health” implies that CKD is associated with an increased risk of progression to end-stage renal disease (ESRD) requiring renal replacement therapy, which is the best-known consequence of CKD.